Welding technical communication teaching and learning embodied knowledge - Mackiewicz, Jo (SUNY series, Studies in scientific and technical communication., 2022)
"Explores the teaching and learning of welding through two narratives: the personal narrative, relating the author's experience as a woman learning how to weld, and the academic narrative examining how instructional communication informs students' embodied knowledge and enculturation into a community of practice"--